A BODIPY-PHENOL-BASED SENSOR FOR SELECTIVELY RECOGNIZING THREE BASIC ANIONS - LV,YONGJUN (Sociedad Chilena de Química, 2015)
A novel BODIPY-based anion sensor 1 bearing di-tert-butyl phenol unit was designed and prepared. In the presence of three basic anions F-, AcO- or H2PO4-, 1 exhibited two novel partially overlapped red-shift absorption bands at 718 nm and 757 nm, respectively. The formation of allotropie structures, after deprotonation of phenol OH, is responsible for these two emerging bands. Fluorescence quenching was also observed due to intramolecular charge transfer (ICT) from phenolate to BODIPY core. As results revealed, the anion affinity mainly depended on the acidity of binding site OH and the basicity of the target anion. Moreover, two bulky tert-butyl groups cannot effectively exclude the approach of large anions to phenol OH, but can facilitate the formation of allotropic resonance structures.